2016
DOI: 10.1038/srep39104
|View full text |Cite|
|
Sign up to set email alerts
|

Perceptual learning to discriminate the intensity and spatial location of nociceptive stimuli

Abstract: Accurate discrimination of the intensity and spatial location of nociceptive stimuli is essential to guide appropriate behaviour. The ability to discriminate the attributes of sensory stimuli is continuously refined by practice, even throughout adulthood - a phenomenon called perceptual learning. In the visual domain, perceptual learning to discriminate one of the features that define a visual stimulus (e.g., its orientation) can transfer to a different feature of the same stimulus (e.g., its contrast). Here, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 50 publications
(62 reference statements)
1
12
0
Order By: Relevance
“…Finally, our findings inform a parallel debate about the localization of nociceptive cortex with a similar and longstanding discussion about the relative importance of somatosensory and insula cortices. There is sufficient evidence that nociceptive sensation involves fine-discriminative processing to imply cortical processing ( Mancini et al, 2012 ) and perceptual learning has been observed recently for nociceptive stimuli ( Mancini et al, 2016 ). It is even possible that there might be different loci for different submodalities of pain (heat, cold, mechanical, inflammatory pain, etc.).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, our findings inform a parallel debate about the localization of nociceptive cortex with a similar and longstanding discussion about the relative importance of somatosensory and insula cortices. There is sufficient evidence that nociceptive sensation involves fine-discriminative processing to imply cortical processing ( Mancini et al, 2012 ) and perceptual learning has been observed recently for nociceptive stimuli ( Mancini et al, 2016 ). It is even possible that there might be different loci for different submodalities of pain (heat, cold, mechanical, inflammatory pain, etc.).…”
Section: Discussionmentioning
confidence: 99%
“…The laser device continuously samples the skin temperature at the stimulation site so that it can adjust its output energy to reach and maintain the target temperature. Importantly, this device can deliver stimuli lasting several seconds and is thus optimal for exploring the perceptual correlates of relatively slow increases and decreases in nociceptive input (Mancini et al 2016). The laser beam was transmitted through an optic fiber, and its diameter was set to 6 mm (28 mm 2 ) by focusing lenses.…”
Section: Methodsmentioning
confidence: 99%
“…Alternatively, other regions might have no role in the cause or expression of chronic pain, but instead reflect consequential (i.e. downstream) changes, for example perceptual learning of a new sensory environment in which pain is more common ( Mancini et al , 2016; Mano et al , 2017). Such regions might be expected to manifest later, and resolve with successful pain treatment ( Rodriguez-Raecke et al , 2009).…”
Section: Discussionmentioning
confidence: 99%